Fabrication of electrocatalytic anode by surface treatment of 4J40 INVAR alloy for feasible water splitting. (19th March 2023) - Peng, Jianying; Lin, Li; Chen, Xi; Wan, Rongchun; Fu, Liming; Shan, Aidang; Chen, Lijia
Abstract: A binder-free, self-supporting and substrate-rejuvenating electrocatalytic electrode based on nonnoble elements is widely acknowledged as the most potential candidate for feasible water splitting. Through the consecutive surface treatment including Fe-leaching in a simple KSCN solution, anodic polarization and chronopotentiometric aging in KOH solution, a commercially available 4J40 INVAR alloy was adopted in this work to fabricate an anode for oxygen evolution in alkaline media. Featuring all above advantages over most state-of-the-art OER electrocatalysts, the 4J40 electrode after being stabilized by CP-aging needs an overpotential of only 241 mV to achieve the current density of 10 mA cm −2 in 1 M KOH, in addition to its stability tested at the lower and higher current densities, respectively. The controlling OER mechanisms were discussed accordingly, with the Fe-doped nickel-based oxyhydroxide and the nickel peroxide being considered correspondingly as the main OER-enhancing species before and after CP-aging. Graphical abstract: Image 1 Highlights: 4J40 INVAR alloy was Fe-leached in KSCN solution to modulate Ni/Fe ratio. OER-active (oxy)hydroxides were obtained on alloy surface by LSV polarizations. Anode based on this alloy was stabilized by CP-aging for efficient and stable OER. Oxyhydroxide and peroxide are OER-enhancing respectively before and after CP-aging. Current density of 10 mA cm −2 was attained at overpotential of 241 mV in 1 M KOH.